Incidence of metabolic syndrome and related diseases in the Khisêdjê indigenous people of the Xingu, Central Brazil, from 1999-2000 to 2010-2011 - Lalucha Mazzucchetti; Patrícia Paiva de Oliveira Galvão; Mario Luiz da Silva Tsutsui; Kennedy Maia dos Santos; Douglas Antônio Rodrigues; Sofia Beatriz Mendonça; Suely Godoy Agostinho Gimeno (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
The aim of this study was to identify the incidence of metabolic syndrome and related diseases in the Khisêdjê population living in the Xingu Indigenous Park, Mato Grosso State, Brazil, from 1999‐2000 to 2010‐2011. The study included 78 individuals aged ≥20 years. Data were analyzed using Student t test, linear regression, and Poisson regression. In 10 years of follow-up, cumulative incidence rates were 37.5% for metabolic syndrome, 47.4% for hypetriglyceridemia, 38.9% for arterial hypertension, 32% for central obesity, 30.4% for excess weight, 29.1% for hypercholesterolemia, 25% for low HDLc, 10.4% for high LDLc, and 2.9% for diabetes mellitus. Age proved to be a risk factor for incidence of hypertension, diabetes, and elevated LDLc, regardless of gender; male gender was a protective factor against incidence of central obesity, independently of age. The study showed deterioration of most target health indicators and exposure of the Khisêdjê to high cardiometabolic risk. These results may be related to changes in traditional lifestyle.